Kontribusi Pemanfaatan Perpustakaan Sekolah dan Motivasi Belajar terhadap Peningkatan Hasil Belajar Geografi Siswa SMA - Nurul Mustovidah; Teguh Pribadi; Marni Marni (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2018)
There is the general consensus regarding the school library utilization and the learning motivation have a contribution to the learning outcome. Neverthenless, both the school library utilization and the learning motivation increase learning outcome remain were not answered, especially at public senior high school students in Palangka Raya. Some research in this study was conducted still partially and only have few students involved. The purpose of this study was to test contribution of school library utilization and learning motivation to geography learning outcome for state senior high schools 4 Palangka Raya. On the data survey on 115 participants - students of X grade of major social science in SMA Negeri 4 of Palangka Raya was chosen, a questionnaire of the school library utilization and the learning motivation was distributed. Besides, results of the formative test were adopted to measure learning achievement of geography subject. All scores were obtained then ranked in three classes. A multiple linear regression was performed to test contribution two independent variables on learning outcome of geography subject. We find the school library utilization contribute to learning outcome but not in learning motivation. In addition, the school library utilization and the learning motivation enhance effectively on learning outcome of geography subject although less. However, further studies on the school library contribution as learning resources are highly recommended to support present study.DOI: http://dx.doi.org/10.17977/um017v23i22018122